Progressive muscle relaxation to reduces chronic pain in hemodialysis patient - Hasbi, Habid Al; Chayati, Nur; Makiyah, Sri Nabawiyah Nurul (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2020)
Background: Hemodialysis is a kidney replacement therapy, but it has many complications identified, one of them is pain. Thus, we need non-pharmacological interventions that can be done by nurses, among them is progressive muscle relaxation (PMR), which is economically-efficient and no side effects. Objective: To determine the effect of progressive muscle relaxation on pain in hemodialysis patients. Methods: This is a quasi experimental design of time series design. The number of samples was 100 patients taken by simple random sampling. Progressive muscle relaxation (PMR) was given every day for 4 weeks. Research instrumentÂ  applied was Brief Pain Inventory. The data analysis employed independent t-test. Results: There was a decrease in pain level from week to week after the intervention, from the scale of 6 (moderate pain) to scale 3 (mild pain). There was a difference in the level of pain between the intervention group and the control group p <0.001. Conclusion: The therapy of non-pharmacological using a progressive muscle relaxation is proven to reduce pain in hemodialysis patients.